Patterns of population and employment change in Shanghai in the 1990s: A zonal analysis with international comparisons. - Zhu, Yu (International Development Planning Review, 2006)
Dividing Shanghai into the core, the inner zone and the outer zone, this paper examines its spatial changes in population and employment in the 1990s, compares them with those in some Asian mega-urban regions, and explores the underlying factors behind those changes and differences. The study shows that the population grew the fastest in the inner zone, resembling the situation in the Asian mega-urban regions. However, the core in Shanghai experienced the greatest change in employment structure, and maintained relatively strong population growth, so differing from those of Asian mega-urban regions. The spatial patterns of population growth, migration and employment changes suggest that while Shanghai experienced an unprecedented movement of its population and industries from the core to the periphery areas, such shifts are limited compared with other Asian mega-urban regions, and its suburbanisotion process and the development of advanced service industries are still in the embryonic stage. These results have important implications for the study of demographic and economic urban processes in Asian mega-urban regions, and for spatial planning in Shanghai's future development. Reprinted by permission of the publisher.